Synthesis, Spectral, Magnetic and Antibacterial Properties of Copper(II) Complexes of Quaternary and Tertiary N-Donor Ligands - Shanmukhappa, S.; Desai, G.P.; Srinivasa, U. (Asian Journal of Chemistry, 2010)
New complexes of Cu(II) with propantheline bromide [PP Bromide] with quaternary nitrogen and amitriptyline hydrochloride [AMTHCl] with tertiary nitrogen were prepared and their structures were elucidated by elemental analyses, IR, 1H NMR, electronic spectra, ESR spectra and conductivity measurements. The spectral data suggest the monodentate nature in the complexes, a tetragonally distorted octahedral geometry is proposed for the complexes. The results of the antibacterial activity studies show that the complexes strongly inhibit Eschearichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella.